Asymmetric Copolymers: Synthesis, Properties, and Applications of Gradient and Other Partially Segregated Copolymers. Issue 19 (16th September 2018) - Zhang, Junliang; Farias‐Mancilla, Barbara; Destarac, Mathias; Schubert, Ulrich S.; Keddie, Daniel J.; Guerrero‐Sanchez, Carlos; Harrisson, Simon
Abstract: Asymmetric copolymers are a class of materials with intriguing properties. They can be defined by a distribution of monomers within the polymer chain that is neither strictly segregated, as in the case of block copolymers, nor evenly distributed throughout each chain, as in the case of statistical copolymers. This definition includes gradient copolymers as well as block copolymers that contain segments of statistical copolymer. In this review, different methods to synthesize asymmetric copolymers are first discussed. The properties of asymmetric copolymers are investigated in comparison to those of block and random counterparts of similar composition. Finally, some examples of applications of asymmetric copolymers, both academic and industrial, are demonstrated. The aim of this review is to provide a perspective on the design and synthesis of asymmetric copolymers with useful applications. Abstract : Asymmetric copolymers are an intriguing class of materials that include gradient copolymers and block copolymers that contain segments of statistical copolymer. This review discusses their synthesis, properties, and some emerging applications.